Acerca de um suporte de lareira do povoado pré-histórico de Leceia (Oeiras) - Cardoso, João Luís (2017)
Discussion and notes about a ceramic artifact of the Estremadura's Early Copper Age, to which the author subscribes the function of ''tire place support".